2014
DOI: 10.1515/zfsoz-2014-0404
|View full text |Cite
|
Sign up to set email alerts
|

Bildungsherkunft und Promotionen: Wie beeinflusst das elterliche Bildungsniveau den Übergang in die Promotionsphase? / Social Background and PhDs: How Does the Educational Background of Parents Affect the Likelihood of Entering Doctoral Studies?

Abstract: Zusammenfassung: Dieser Beitrag behandelt den Zusammenhang zwischen der Bildungsherkunft von Universitätsabsol-vent(inn)en und der Wahrscheinlichkeit einer Promotionsaufnahme nach dem Studium. Auf der Basis einer bundesweit repräsentativen Absolvent(inn)enstudie wird erstens überprüft, inwieweit beim Übergang in die Promotionsphase herkunftsspezifische Unterschiede bestehen, und zweitens, welche Prozesse und Mechanismen zu diesen Unterschieden füh-ren. Die Analysen zeigen, dass die Wahrscheinlichkeit der Aufna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Transitions into PhDs and further into academia are much less well studied than lower-level transitions. Nevertheless, studies based on survey data from the US (Mullen, Goyette, & Soares, 2003), the UK (Wakeling & Laurison, 2017), Canada (Zarifa, 2012), Italy (Argentin & Triventi, 2011) and Germany (Jaksztat, 2014) suggest that high-SES graduates are more likely to transition to the postgraduate level. Triventi (2013) arrives at different conclusion.…”
Section: Inequalities In Academiamentioning
confidence: 99%
“…Transitions into PhDs and further into academia are much less well studied than lower-level transitions. Nevertheless, studies based on survey data from the US (Mullen, Goyette, & Soares, 2003), the UK (Wakeling & Laurison, 2017), Canada (Zarifa, 2012), Italy (Argentin & Triventi, 2011) and Germany (Jaksztat, 2014) suggest that high-SES graduates are more likely to transition to the postgraduate level. Triventi (2013) arrives at different conclusion.…”
Section: Inequalities In Academiamentioning
confidence: 99%
“…However, for German academia, there is some empirical evidence of inequality. On the one hand, a large body of research has shown that there are social inequalities by gender and parental academic background-which is one of the main dimensions of an individual's social origin-in the participation in and the completion of higher education (e.g., Becker 2009;Jaksztat 2014;Jaksztat et al 2021;Lörz 2019; Lörz/Mühleck 2019; Lörz/Schindler 2016; Müller/Pollak 2016; Müller et al 2011;Vogel 2017;Watermann et al 2014); some studies also found inequalities by migration background (Lörz 2019(Lörz , 2020). Yet individuals who have earned an advanced higher education degree seem to be such a preselected group (Mare 1980) that these inequalities no longer persist (Bornmann/Enders 2004;König et al 2021;Lörz/Mühleck 2019;Lörz/Schindler 2016;Zimmer 2021).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of primarily quantitative studies on the German context shed light on class-specific inequalities in the distribution of doctorates by demonstrating an influence of social origin on the intention to participate in a doctoral program (Lörz/Seipelt 2019), doctoral admissions in general (Bachsleitner et al 2020;Jaksztat 2014;Jaksztat/Lörz 2018;Radmann et al 2017) or admissions to different forms of doctorates (de Vogel 2017). The German academic system has been described as a winner-takes-all market (Berthoin Antal/Rogge 2020), and the career trajectory as an "Up or Out" model (Fitzenberger/Schulze 2014).…”
Section: Introductionmentioning
confidence: 99%